2021
DOI: 10.1101/2021.05.31.21258122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The potential impact of vaccine passports on inclination to accept COVID-19 vaccinations in the United Kingdom: evidence from a large cross-sectional survey and modelling study

Abstract: Background: Four vaccines against the novel coronavirus 2019 disease (COVID-19) caused by the severe acute respiratory coronavirus 2 (SARS-CoV-2) have currently been approved for use in the United Kingdom. As of 30 April 2021, over 34 million adults have received at least one dose of a COVID-19 vaccine. The UK Government is considering the introduction of vaccine passports for domestic use and to facilitate international travel for UK residents. Although vaccine incentivisation has been cited as a motivating f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This is in line with previous research that shows the majority of vaccine-hesitant individuals do not approve a mandatory policy for the COVID-19 vaccine 35. Additionally, mandating vaccines can increase anger and negative attitudes among vaccine-hesitant individuals, leading to reduced vaccination intentions and uptake,36–39 and potential stigmatisation of those who refuse to have the vaccine 40. However, despite some participants stating they would leave their job rather than get the vaccine, we do not know how this intention may or may not translate to actual behaviour.…”
Section: Discussionsupporting
confidence: 77%
“…This is in line with previous research that shows the majority of vaccine-hesitant individuals do not approve a mandatory policy for the COVID-19 vaccine 35. Additionally, mandating vaccines can increase anger and negative attitudes among vaccine-hesitant individuals, leading to reduced vaccination intentions and uptake,36–39 and potential stigmatisation of those who refuse to have the vaccine 40. However, despite some participants stating they would leave their job rather than get the vaccine, we do not know how this intention may or may not translate to actual behaviour.…”
Section: Discussionsupporting
confidence: 77%
“…This study found that socio-demographic background is strongly associated with intent to accept the vaccine, with females, younger age groups, Muslims and 'other' religions, and Black and 'other' ethnicities, and non-English speakers less likely to state an intent to vaccinate than their respective baseline groups. While many of these associations had been found at the time of this analysis for both existing immunisation programmes [34][35][36][37] and a COVID-19 vaccine 19,38,39 , recent evidence has suggested that COVID-19 vaccine passports may drive lower vaccination sentiment in the UK 40,41 . In particular, lower sentiment is evidenced in groups with low COVID-19 vaccine confidence, which includes young adults, males, those with Black/Black British ethnicity (a result also found in US populations 42 ), as well as highly educated groups 40 : this is a plausible explanation for London's MRP forecasts lagging observed uptake, opposing broader national trends.…”
Section: Discussionmentioning
confidence: 80%
“…In particular, lower sentiment is evidenced in groups with low COVID-19 vaccine confidence, which includes young adults, males, those with Black/Black British ethnicity (a result also found in US populations 42 ), as well as highly educated groups 40 : this is a plausible explanation for London's MRP forecasts lagging observed uptake, opposing broader national trends. Vaccine passport policies have typically been found to be polarising, increasing uptake intentions in some groups but reducing them in others 40,42 : of particular concern in ongoing and future vaccination campaigns is whether these one-size-fits-all policies have enhanced resistance in areas with low vaccine confidence, which may pose challenges for achieving local and national herd immunity targets 22 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Governments such as UK Government are already considering the introduction of vaccine passports for domestic use and to facilitate international travel for UK residents (de Figueiredo, Larson and Reicher, 2021). While this may only be focusing on the UK, it means other countries that may need their citizens to travel to the UK may be required to produce such vaccine passports.…”
Section: Adoption Of Immunisation Databases For Covid-19 Vaccinesmentioning
confidence: 99%